2020
DOI: 10.1177/0961203320903080
|View full text |Cite
|
Sign up to set email alerts
|

Ocular involvement in systemic lupus erythematosus patients: a paradigm shift based on the experience of a tertiary referral center

Abstract: Objective To evaluate ocular involvement in a cohort of systemic lupus erythematosus (SLE) patients of a tertiary referral center and to compare the results with the existing literature. Methods Patients underwent a complete ophthalmological evaluation, including visual acuity, slit-lamp examination, fluorescein staining, Schirmer-I test, Goldmann applanation tonometry, fundoscopy, 10-2 automated threshold visual fields, fundus autofluorescence and spectral-domain optical coherence tomography to screen for hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
2
10
2
1
Order By: Relevance
“…The most common findings among patients with retinopathy were cotton-wool spots, retinal hemorrhage, and Roth spots, which is in line with previous studies [ 3 , 4 , 6 , 8 11 , 13 ]. All of these pathologies reflect vascular damage.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The most common findings among patients with retinopathy were cotton-wool spots, retinal hemorrhage, and Roth spots, which is in line with previous studies [ 3 , 4 , 6 , 8 11 , 13 ]. All of these pathologies reflect vascular damage.…”
Section: Discussionsupporting
confidence: 91%
“…Seth et al reported similar findings, and also reported a higher incidence of autoimmune hemolytic anemia in SLE patients with retinopathy [ 7 ]. Similar to previous reports, we found that patients with retinopathy have lower C3 and C4 concentrations, and have higher levels of ANA and Anti-dsDNA, findings which indicate an antibody-mediated retinal damage pathogenesis [ 1 6 , 8 11 , 13 , 17 ]. Urine casts were also significantly more prevalent in patients with retinopathy.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations